2020
DOI: 10.22437/bio.v6i1.8642
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Booklet Tumbuhan Paku di Taman Hutan Raya Sultan Thaha Syaifuddin Sebagai Bahan Pengayaan Mata Kuliah Taksonomi Tumbuhan

Abstract: The research aims to develop and determine the feasibility of nail plant booklets in Tahura STS. This type of research is Research and Development research using ADDIE learning design models. The booklet that was developed contains 42 types of nails that grow in Tahura STS, consisting of 14 types of epipitic nails and 28 types of terrestrial nails. The booklet that was developed contains scientific names, pictures, classifications and descriptions of ferns that grow in Tahura STS. Validation of media experts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…This demonstrates that the practical guide is interesting in terms of design, applicability, and clarity of the graphics and photos offered that can stimulate students' interest in reading and studying the reaction rate content. The existence of a coherent combination of colors, letters, and images can provide the reader with an overview of the content so that it can stimulate their interest (Muswita et al, 2020). It is similar to a study who found that students were indeed interested in studying the content if it is presented in an attractive and understandable way (Istifarida et al, 2017).…”
Section: Discussionmentioning
confidence: 56%
“…This demonstrates that the practical guide is interesting in terms of design, applicability, and clarity of the graphics and photos offered that can stimulate students' interest in reading and studying the reaction rate content. The existence of a coherent combination of colors, letters, and images can provide the reader with an overview of the content so that it can stimulate their interest (Muswita et al, 2020). It is similar to a study who found that students were indeed interested in studying the content if it is presented in an attractive and understandable way (Istifarida et al, 2017).…”
Section: Discussionmentioning
confidence: 56%
“…And as for the input given focusing on the writing procedure, this follows Fadil et al ( 2017) mention if the suitability of the type and size of the letters used affects the readability of the media so that it is easy for readers to read. In addition, Muswita et al (2020) added that combining colors and images influence readers' interest in reading. So that the background cover must have a bright color, avoid placing excessive photos because it can confuse readers in focusing on the writing or the image.…”
Section: Resultsmentioning
confidence: 99%
“…Bahan ajar berupa buku teks tebal membuat peserta didik merasa bosan untuk membaca dan bahasa yang digunakan sulit dipahami (Muswita et al, 2020). Kemudian tidak adanya integrasi potensi lokal yang sesuai dengan konteks materi plantae mengakibatkan pemberian contoh menjadi kurang kontekstual dengan kehidupan.…”
Section: Pendahuluanunclassified